AKAL DAN WAHYU DALAM PEMIKIRAN M. QURAISH SHIHAB - Yuhaswita Yuhaswita (JURNAL ILMIAH SYI'AR, 2017)
Reason according to M. Quraish Shihab sense is the thinking power contained in man and is a manipation of the human soul. Reason is not understood materially but reason is understood in the abstract so that sense is interpreted a thinking power contained in the human soul, with this power man is able to gain knowledge and be able to distinguish between good and evil. Revelation according to M. Quraish Shihab, is the delivery of God’s Word to His chosen people to be passed on to human beings to be the guidance of life. God’s revelation contains issues of aqidah, law, morals, and history. Furthermore, M. Quraish Shihab reveals that human reason is very limited in understanding the content of Allah’s revelation, because in Allah’s revelation there are things unseen like doomsday problems, death and so forth. The function of revelation provides information to the sense that God is not only reachable by reason but also heart.